In vitro inhibition of acetylcholinesterase by acephate and methamidophos - Mohamad, Rosli (Malaysian Plant Protection Society, 1990)

(untitled)
Inhibition of the acetylcholinesterase (AChE) of two insects, laboratory rat and human by acephate and methamidophos insecticides was evaluated in vitro. Acephate in itself is capable of inhibiting AChE to some extent, immediately as well as for a prolonged period. The inhibition by methamidophos progressed faster during the first 20 to 30 min of exposure, but not immediately. The pattern of inhibition of the AChE by both insecticides followed that of paraoxon, and are non-reversible. Incubation of AChE with acephate and methamidophos together did not produce inhibition of synergistic effect but could only be considered as additive